(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An attempt has been made to investigate the heat and mass transfer through a porous medium in the presence of Magnetohydrodynamic flow and chemical reaction. On the basis of certain assumptions, the momentum, energy and concentration equations are obtained. These governing equations are transformed into ordinary differential equations using self-suitable transformations and these resulting equations are solved numerically using shooting procedure with fourth order Runge-Kutta Method. The effect of various non- dimensional parameters like magnetic parameter (M), Schmidt number (Sc), Chemical reaction (Kr) are discussed with the help of graphs.